Toward Sustainable Preservation of Cultural Heritage Buildings: A Combination of Digital Mapping and Architectural mapping for Omah Pencu in the Historic Area of Kudus Kulon - Atik Suprapti; Anang Wahyu Sejati; Agung Budi Sardjono; Edward E. Pandelaki; Abdul Malik; Nurma Mediasri Huwaida (TEKNIK, 2020)
This study aims to map the existence of the wooden houses of Omah Pencu and classifies their potencies as heritage buildings in the historic area of Kudus Kulon. Caring for indigenous cultural heritage will contribute to the strengthening of local identity. The traditional houses of Omah Pencu have been developing as the specific architecture since the end of the 17'th century, as a living place of the ‘Gusjigang' community, and artifacts evident of the city heyday. However, the pressure of modernization-capitalization in the city caused several changes in their built environment and decreased the number of Omah Pencu. This research concern with the GIS interpretation methods and the direct observations use the questionnaire, interview, and architectural documentation. The findings provide an important database for preservation in the digital era. The digital mapping, combined with the mapping of tangible and intangible buildings, produces digital information about the Omah Pencu building condition that has never been done before. Through this mapping, found that the participation effort of the community caused the sustainability of preservation. It is a very significant bottom-up participation.  However, toward sustainable preservation, a strategy, planning, design, and management that integrated all stakeholders and resources by utilizing digital technology are needed.